2021
DOI: 10.3390/fermentation7040238
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Lactobacillus paracasei HY7017 Capable of Improving Physiological Properties and Immune Enhancing Effects Using Red Ginseng Extract

Abstract: Red ginseng has powerful potential for use as a prebiotic, but its use is limited due to its antibacterial activity. The aim of this study is to present panax ginseng’s endophytic lactic acid bacteria capable to overcome the antibacterial activity of red ginseng and improve their characteristic. Lactobacillus paracasei HY7017 (HY7017) was cultured in a medium supplemented with red ginseng. The probiotic properties and immune-enhancing effects of HY7017 were investigated in vitro and in vivo. HY7017 was prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Spleen is a significant organ in terms of understanding immune cell subpopulations and their immune responses to antigens. Splenocytes include T and B cells, macrophages, and natural killer (NK) cells [ 34 ]. Their immune responses include antigen presentation, T lymphocyte activation, and B lymphocyte differentiation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spleen is a significant organ in terms of understanding immune cell subpopulations and their immune responses to antigens. Splenocytes include T and B cells, macrophages, and natural killer (NK) cells [ 34 ]. Their immune responses include antigen presentation, T lymphocyte activation, and B lymphocyte differentiation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…NO secreted by macrophages also induces immune cell activation and promotes resistance to pathogens (Hu et al, 2021). Mo et al (2021) observed that Lacticaseibacillus paracasei HY7017 cultivated in 3% RGE-supplemented medium dramatically boosted NO production. In addition, the mRNA level of iNOS, a key enzyme in NO synthesis, and COX-2 were higher after treatment with HY7017-RGEs.…”
Section: Macrophagesmentioning
confidence: 99%
“…In addition, the mRNA level of iNOS, a key enzyme in NO synthesis, and COX-2 were higher after treatment with HY7017-RGEs. This process had no effect on the secretion of the anti-inflammatory cytokine IL-10, indicating that fermented red ginseng enhanced the immune response without creating excessive inflammation ( Mo et al, 2021 ).…”
Section: Immunoregulatory Mechanism Of Lactic Acid Bacteria-fermented...mentioning
confidence: 99%
“…Therefore, using ginseng and LAB together as materials for health functional food can provide a synergistic effect that will help to improve overall health and well-being. Moreover, as Panax ginseng has been reported to have high antibacterial activity [ 17 , 18 ], the isolation of potential probiotic strains derived from ginseng is of growing importance [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%